The image of Alexander the Great in the poem by Abai Kunanbayuly - Aigul S. Kenzhegulova, Zhanbota T. Karipbaev, Seit A. Kaskabasov, (Opción, 2020)
This article is devoted to the study of the work of the great Kazakh poet Abai Kunanbayuly. In the course of the study, the works of prominent Russian-Soviet orientalists V.V. Bartold, E.E. Bertels, and I.S. Braginsky were used. Based on a comparative analysis, the corresponding conclusions were drawn on the artistic-figurative component of many works written on the theme of Iskander. The features and differences of medieval and national literature in the interpretation of the same image are revealed. The versatility and the humanistic spirit of Abai’s creativity in the context of his poem are shown.